Testing field adaptation strategies for delaying grape ripening and improving wine composition in a cv. Macabeo Mediterranean vineyard - Buesa, Ignacio; Yeves, Antonio; Guerra, Diego; Sanz, Felipe; Chirivella, Camilo; Intrigliolo, Diego S. (Frontiers in Plant Science, 2023)
Under semi-arid and warm climates, field practices for climate change adaptation have to be defined in order to modulate grape composition according to the desired wine styles. Under this context, the present research investigated several viticulture practices in cv. Macabeo for Cava production. The experiment was carried out over three years in a commercial vineyard located in the province of Valencia (eastern Spain). The techniques tested were: i) vine shading, ii) double-pruning (bud forcing) and iii) the combined application of soil organic mulching and shading, all of them tested against a control. Double-pruning significantly modified phenology and grape composition, improving the wine alcohol-to-acidity ratio and reducing the pH. Similar results were also achieved by shading. However, the shading strategy did not significantly affect yield, unlike double-pruning, which reduced vine yield even in the year following its application. Shading alone or in combination with mulching significantly improved vine water status, suggesting that these techniques can also be used to alleviate water stress. Particularly, we found that the effect of soil organic mulching and canopy shading on stem water potential was additive. Indeed, all the techniques tested were useful for improving wine composition for cava production, but double-pruning is only recommended for premium Cava production.